Review and Prospect of the Promotion of Agroforestry System Technology in Southern Collective Forest Areas - Zhang Xue, (International Journal of Engineering and Management Research, 2023)
The promotion of agroforestry technology in undergrowth cultivation can alleviate the degradation of forest land. However, the slow progress in the implementation of this technology has become a concern for decision-makers and the academic community. This article systematically reviews the main policies and evaluations of the implementation effects of undergrowth agroforestry technology, and identifies the possible constraints on the policy implementation. It also provides prospects for future research directions, offering insights for policy improvements and references for related studies. The research findings indicate that undergrowth agroforestry technology not only affects the economic benefits of rural households but also contributes to ecological benefits such as soil erosion control and reduction of chemical fertilizer use. However, the effectiveness of undergrowth agroforestry technology is constrained by various factors, including resource endowment, household characteristics, and external environment. Lastly, there is a need for further investigation into the deepening and optimization of the promotion of undergrowth agroforestry technology.